Implementasi Sifat Amanah Pengelola Koperasi Pondok Pesantren (Studi Kasus Pada Pengelola Koperasi Pondok Pesantren Qomaruddin Kecamatan Bungah Kabupaten Gresik - Abiyoga, Firdaus Arfianandy; Zaki, Irham (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
A Muslim who works as a form of workship to Allah SWT make attempts to obtain wealth by means of the lawful and good. As well as within the organization, a Muslim who gained the trust of the other party will always manage cooperatives by prioritizing and applying traits according to traits owned by Rasulallah, one of which is the trusthworthy traits and is able to provide a positive influence to others within the organization.The research method used is case study with a qualitative descriptive approach. This study uses interviews in primary data collection. The scope of research is limited to the focus on the cooperative manager of Qomaruddin boarding school Sampurnan Bungah in Gresik and find answers on how to implement the trustworthy traits of Rasulalllah on the management of the cooperative.The result of this research is the implementation of the trustworthy traits of Rasulallah SAW has already been implemented properly by the cooperative manager of the cooperative boarding school in the form of cooperative management in accordance with Islamic principle, because the cooperative management fullfilled with the 3 indicators such as responsibility, trusworthiness and transparency so that the growth and development of cooperative boarding school survived until today. The manager of the boarding school cooperative that implements the trustworthy traits of Rasulallah able to make policy and ethical Islamic system which resulted in an Islamic organization. The cooperative management has implemented the trustworthy traits correctly, by implementing those trustworthy traits, kopontren obtain the benefit. Kopontren manager interpret the business benefits based on the blessing of sustenance and pleasure of Allah SWT from the management as well as the ability and the sincerity to provide benefits to many parties.